(untitled) (Bangladesh Journal of Plant Taxonomy, 2014)
The present study explored the use of internal transcribed spacers (ITS) sequences (ITS1-5.8S-ITS2) of nuclear ribosomal DNA (nrDNA) for identification of Echinops mandavillei Kit Tan, an endemic species to Saudi Arabia. The sequence similarity search using Basic Local Alignment Search Tool (BLAST) and phylogenetic analyses of the ITS sequence of E. mandavillei Kit Tan showed high level of sequence similarity (98%) with E. glaberrimus DC. (section Ritropsis). The novel primary sequence and the secondary structure of ITS2 of E. mandavillei could have a potential use for molecular genotyping. DOI: http://dx.doi.org/10.3329/bjpt.v21i1.19256 Bangladesh J. Plant Taxon. 21(1): 33-42, 2014 (June)